Implementation of Storytelling Method to Improve Students' Understanding of the Stories of the Prophets and Apostles at RA Ar Rahman - Khoiroh, Muhimatul (MANDAILING GLOBAL EDUKASIA, 2025)
Islamic religious education plays an important role in shaping the character and morals of students from an early age. One of the materials taught at the Raudhatul Athfal level is the story of the Prophet and the Apostle, which aims to instill the values ​​of faith and exemplary behavior in everyday life. However, monotonous delivery methods often lead to a lack of understanding and interest in the material. Therefore, this study aims to analyze the application of the storytelling method in improving students' understanding of the story of the Prophet and the Apostle at RA Ar Rahman. The research method used is classroom action research with a qualitative approach. The subjects of the study were students of RA Ar Rahman aged 4–6 years. Data were collected through observation, interviews with teachers, and evaluation of student understanding before and after the application of the storytelling method. Data analysis techniques were carried out by means of data reduction, data presentation, and drawing conclusions. The results of the study showed that the storytelling method was able to significantly improve students' understanding of the story of the Prophet and the Apostle. This can be seen from the increase in students' active participation during learning, their interest in listening to stories, and their ability to remember and retell the stories that have been learned. In addition, this method also has a positive impact on the development of students' social and emotional skills, such as increasing empathy and respect for parents and teachers. The application of the storytelling method is carried out using various techniques, such as the use of hand puppets, picture illustrations, and interesting voice expressions to adjust to the characteristics of the child's age. The teacher also invites students to discuss and ask questions after the storytelling session to strengthen their understanding. The obstacles faced in implementing this method include time constraints and the need for training for teachers in improving effective storytelling skills. Thus, the storytelling method can be an effective alternative in improving students' understanding of the story of the Prophet and the Apostles. The application of this method not only makes learning more enjoyable, but also helps students absorb the moral values ​​contained in the story. Therefore, it is recommended that this method continue to be developed and applied more widely in Islamic religious learning at the early childhood education level.